Hubungan Aktivitas Fisik Dengan Indeks Massa Tubuh Pada Anak Usia Sekolah 7-12 Tahun di UPTD SD Negeri 93 Barru - Masdalis Masdalis (NHM PRESS, 2023)
The era of globalization causes changes in behavior that cause an imbalance between physical activity and food intake. Low physical activity is one of the factors increasing body mass index (BMI). As a result of relatively low physical activity causes an increase in the body mass index (BMI) increase. The purpose of this study was to determine the relationship between physical activity and body mass index of school children aged 7-12 years at UPTD SD Negeri 93 Barru. This type of research is a quantitative study with a cross-sectional approach. The sample in this study was school-age children 7-12 years at UPTD SD Negeri 93 Barru. Data collection was carried out using a stamping scale, microtoise, and a PAQ-C questionnaire. Sampling was carried out using the probability sample method where in a population of 132 students a sample of 99 was obtained. The results of the study can be concluded that the activity level of students tends to be low, both at school and at home. Based on the results of the Fisher's exact test which was carried out using the cross tab method, a significant value of 0.010 was obtained, this indicated that the p-value was <0.05. This means that there is a relationship between the two variables.